Fundamentals Of Entrepreneurship (ENT300) : Asian kitchen food and beverage / Abdul Haadi Nur Abdul Razak ... [et al.] - Abdul Razak, Abdul Haadi Nur; Henery, Esmiesha; Mohamad Rosli, Ieffa Rozlin; Bakeri, Iffah Marwati; Samsu, Shahmy Haziq (2019)
Asian Kitchen is the new cafe that is not yet exist in Kuching. Sarawak which provide food services. We all can see that fmtn the company's name shows that we are focusing on the Asian kind of food. In this case, we are positioning our products in customer's mind until they can remember our company's name which is simple and easily to pronounce.